2000
DOI: 10.2337/diacare.23.11.1648
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative triglycerides predict post-coronary artery bypass graft survival in diabetic patients: a sex analysis.

Abstract: A sex analysis O R I G I N A L A R T I C L EOBJECTIVE -Hypertriglyceridemia is commonly observed in association with diabetes. Despite cross-sectional studies and isolated longitudinal analyses in patients without coronary artery disease, the suggestion that triglyceride levels are relevant to subsequent cardiovascular events in the setting of diabetes remains controversial. This study evaluates the predictive value of serum triglyceride levels on mortality in post-coronary artery bypass graft (CABG) diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…It is plausible that increased serum triglycerides convey a higher mortality in diabetic women than in men, since increased triglycerides predict cardiovascular disease more consistently in women (40,41). One possible explanation is that women with type 2 diabetes respond differently to increased levels of serum triglycerides than do diabetic men.…”
Section: Survival In Type 2 Diabetesmentioning
confidence: 77%
“…It is plausible that increased serum triglycerides convey a higher mortality in diabetic women than in men, since increased triglycerides predict cardiovascular disease more consistently in women (40,41). One possible explanation is that women with type 2 diabetes respond differently to increased levels of serum triglycerides than do diabetic men.…”
Section: Survival In Type 2 Diabetesmentioning
confidence: 77%
“…[6][7][8]10 However, are similar risks demonstrated in the acute perioperative setting? Yes, results of this study indicate that half of the CABG patients at our institution have metabolic syndrome, and these patients experience adverse clinical outcomes such as longer postoperative stays www.ajcconline.org Table 2 Demographics by patient's sex and metabolic syndrome characterization infection, decreased tissue and organ perfusion, and compromised wound healing have all been associated with uncontrolled blood sugar levels in hospitalized patients who have undergone surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of individual risk factors that make up this syndrome, such as diabetes and hypertriglycerid emia, increases morbidity and mortality in postoperative CABG patients. 6,7 When these risk factors are examined as a cluster, the presence of metabolic syndrome in CABG patients is predictive of higher rates of occluded vein grafts within 5 years. 8 Metabolic syndrome is also an independent risk factor for atrial fibrillation after CABG surgery.…”
mentioning
confidence: 99%
“…In regard to the greater mortality of women with hypertriglyceridemia, no study in the literature was found relating the elevation in triglycerides to worse results in the in-hospital phase of myocardial revascularization surgery; only references to its later influence were found 44 . The greater mortality in the female sex in the remaining subgroups analyzed did not reach statistical significance, which prevents us from stating that no difference really exists or whether the sample did not reach a sufficient size for demonstrating the difference.…”
Section: Discussionmentioning
confidence: 99%